Targeted Therapies for the Treatment of Pediatric Non-Hodgkin Lymphomas: Present and Future - Caryn E. Sorge; Jenny K. McDaniel; Ana C. Xavier (MDPI AG, 2016)
Pediatric Non-Hodgkin Lymphomas (NHL) are a diverse group of malignancies and as such treatment can vary based on the different biological characteristics of each malignancy. Significant advancements are being made in the treatment and outcomes of this group of malignancies. This is in large part due to novel targeted drug therapies that are being used in combination with traditional chemotherapy. Here, we discuss several new lines of therapy that are being developed or are in current use for pediatric patients with NHL.